Peran Teknologi dan Komunikasi (TIK) Dalam Proses Pembelajaran di MA Miftahul Ulum Kedungpanji - Siti Nurbaiti Nasabiyah; Selvitia Putri Santika; Silvia Putri Indah Puspita; Siti Umi Kholifah; Septyan Kurnia Gandhi; Saad Al Hakim; Nurul Malikah (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
MA Miftahul Ulum Kedungpanji is one of the senior secondary education institutions in Indonesia, which is involved in integrating technology in the learning process. As time goes by, MA Miftahul Ulum Kedungpanji strives to utilize ICT to increase the effectiveness and efficiency of the teaching and learning process. The aim of this research was none other than to determine the role of ICT in the learning process at MA Miftahul Ulum Kedung Panji. It is hoped that this research will provide insight into the effectiveness of applying ICT in the learning process at MA Miftahul Ulum Kedungpanji and provide useful recommendations for improving the quality of education through the use of information and communication technology. This research uses a qualitative approach with observation methods and structured interviews because the questions that will be given to the sources have been prepared in detail before the interview begins. The research results show that at MA Miftahul Ulum Kedungpanji in the use of Communication Technology teachers use LCD projectors and laptops, while the media used in learning such as Power Point, YouTube videos, films, pictures. Apart from that, the madrasa also makes ICT learning a local content in learning that teaches theory and practice. The use of communication technology in learning at Madrasas can certainly make it easier for teachers to deliver learning material in a creative, innovative way and give a positive impression to students which can be seen from the enthusiasm of the students, compared to learning carried out without using IT.